High double burden of child stunting and maternal overweight in the Republic of the Marshall Islands. (24th August 2020) - Blankenship, Jessica L.; Gwavuya, Stanley; Palaniappan, Uma; Alfred, Julia; deBrum, Frederick; Erasmus, Wendy
Abstract: Many low‐ and middle‐income countries are faced with a double burden of malnutrition characterized by a stagnating burden of undernutrition and an increasing prevalence of overweight and obesity often observed both at population and household levels. We used data from the 2017 National Integrated Child Health and Nutrition Survey in the Republic of the Marshall Islands to explore the prevalence of overweight mother‐stunted child pairs (mother–child double burden, MCDB). We used bivariate analysis, multivariate logistic regression, and multinomial logistic regression analysis to explore associations between child‐, maternal‐, and household‐level variables and both stunting and MCDB and other types of maternal–child pairs. Our results indicate that nearly three out of four mothers were overweight or obese and one in four households is home to an overweight mother with a stunted child. The risk of child stunting and of MCDB were largely associated with maternal characteristics of lower maternal height, maternal age at birth, years of education, and marital status and household economic status as measured by wealth index and number of household members. These findings support the growing body of evidence showing that the coexistence of high maternal overweight and child stunting (MCDB) has linked root causes to early life undernutrition that are exacerbated by the nutrition transition.